Development of Socially Responsible Organizations and Social Entrepreneurship: Understanding the Framework of Operations in The European Union - Vlatka BILAS; Sanja FRANC; Matija PUCEK (Communications of International Proceedings, 2024)
By integrating business practices with social mission goals, social entrepreneurship has emerged as a significant approach to addressing societal challenges and generating lasting benefits for communities. This paper explores the operational frameworks and historical evolution of socially conscious enterprises, with a focus on their development within the European Union. While the concept of social responsibility can be traced back to early charitable and community-focused efforts, such as medieval guilds and nonprofit organizations addressing local economic security, these approaches have evolved into institutionalized models that merge business operations with a primary emphasis on social impact and community welfare. Addressing a gap in the literature, this study provides a detailed examination of how policy developments, legal frameworks, and strategic initiatives in the European Union have shaped the growth of social entrepreneurship, promoting inclusive and sustainable economic progress. Methodologically, the paper combines historical analysis with a review of contemporary institutional practices to differentiate between the concepts of social entrepreneurship and social enterprise. The findings underscore the critical role of social enterprises in addressing gaps left by traditional market and public sector approaches, leveraging innovation and community-centred strategies to tackle pressing societal needs. The paper concludes by identifying challenges and potential areas for further development of the strategic and legal framework for social enterprises in the European Union.
Keywords: Social entrepreneurship; socially responsible organizations; European Union